A Roadmap for Craft Understanding, Education, Training, and Preservation - Xenophon Zabulis; Nikolaos Partarakis; Ioanna Demeridou; Paraskevi Doulgeraki; Emmanouil Zidianakis; Antonis Argyros; Maria Theodoridou; Yannis Marketakis; Carlo Meghini; Valentina Bartalesi; Nicolò Pratelli; Christian Holz; et al. (Heritage, 2023)
A roadmap is proposed that defines a systematic approach for craft preservation and its evaluation. The proposed roadmap aims to deepen craft understanding so that blueprints of appropriate tools that support craft documentation, education, and training can be designed while achieving preservation through the stimulation and diversification of practitioner income. In addition to this roadmap, an evaluation strategy is proposed to validate the efficacy of the developed results and provide a benchmark for the efficacy of craft preservation approaches. The proposed contribution aims at the catalyzation of craft education and training with digital aids, widening access and engagement to crafts, economizing learning, increasing exercisability, and relaxing remoteness constraints in craft learning.